Noncontact and High‐Accuracy Smart Thermosensors Based on the Thermal‐Field Resistivity Response of Conducting Polymers. Issue 7 (11th June 2018) - Jiang, Yuqian; Zang, Xiaoling; Wang, Xusheng; Ma, Xinlei; Ji, Junhui; Lu, Conghua; Xue, Mianqi
Abstract: Compared to traditional thermometers, second‐generation (2G) thermosensors with noncontact property have attracted huge interest in practical demands of intelligent life. Hereinto, conducting polymers, widely used in optoelectronic devices, play a significant role in developing such 2G sensors. This is due to their intrinsic unique physical and electrical properties, arising directly from strong intrachain π‐electron delocalization and weak interchain couplings. An innovative progress for the fabrication of conducting polymer‐based smart fiber thermosensors (CPSFT sensors) beyond the traditional contact‐based ones is reported here. The CPSFT sensors work based on the resistivity response of the conducting polymer and light‐emitting diode optical ranging. This CPSFT sensor owns various advantages over traditional ones, such as noncontact, low cost, passive early warning, high accuracy, fast response, wide applications, and facile large‐scale fabrication. These superiorities are in favor of fabricating smart thermal sensors to satisfy the needs in future life, and thus improving the industrialization of hi‐tech but easily prepared 2G thermal sensors. Abstract : Second‐generation (2G) conducting polymer based smart thermosensors are fabricated through the integration of signal feedback control, optical ranging, and visual real‐time early warning systems. The success in fabricating such sensors will bring new reflections and enlightenment to the existing infrared radiation thermometer, thus promoting the industrialization of hi‐tech but easily prepared 2G thermosensors and attracting more researchers into this field.